Gender Differences in Demographic and Clinical Features of Physicians Admitted to a Program for Medical Professionals with Mental Disorders - Braquehais, María Dolores; Arrizabalaga, Pilar; Lusilla, Pilar; Valero, Sergi; Bel, Miquel Jordi; Bruguera, Eugeni; Sher, Leo; Casas, Miquel (Frontiers in Psychiatry, 2016)
Objective: To examine the demographic and clinical differences between men and women admitted to a Physicians’ Health Programme (PHP). Method: Retrospective chart-review of 778 medical records of physicians admitted to the Barcelona PHP from February 1st 1998 until December 31st 2015. Results: Women admitted to the Barcelona PHP were younger than men, were more likely to be self-referred and to be admitted forfor a non-addictive mental disorder. Prevalence of unipolar affective disorders (60.1% vs. 37.6%), adjustment disorders (62.4% vs. 37.6%) and obsessive-compulsive disorder (61.1% vs. 38.9%) was significantly higher among women while prevalence of alcohol use disorders was lower (32.7% vs. 67.3%). Nevertheless, both groups were similar with regards to medical specialty, working status, length of their first treatment episode, and presence of hospitalization during that episode. After multivariate analysis, age, type of referral and main diagnosis (addictive disorders vs. other mental disorders) discriminated the differences between groups. Conclusions: Women physicians seem to be more prone to voluntarily ask for help from PHPs and are more likely to suffer from mood and anxiety disorders compared to men. However, mental disorders’ severity may be similar in both groups. More studies are needed to clarify the gender factors related to this behavior.